Analisis Pola Interaksi Sosial Siswa Di Sekolah Dasar Negeri 1 Pengkelak Mas - hapiz, Abd (FAKULTAS TARBIYAH, 2021)
This study aims to identify and describe the factors that support the occurrence of social interaction among children with difficulty interacting at SD Negeri 1 Pengkelak Mas, Pengkelak Mas Village, Sakra Barat District, East Lombok Regency, NTB Province. This type of research is descriptive and qualitative. The research subjects were children with difficulty interacting in high grades (grades IV, V, VI). Subjects totaled 9 children. The determination of subjects based on children's data is in accordance with the considerations and results of observations made by researchers for the 2020/2021 school year. The method used in collecting data by observation, interviews, and documentation. The method used to analyze the data uses the Huberman & Miles Interactive model. The results showed that the factors that support the social interaction of children with social interaction difficulties are categorized into two, namely Associative social interaction and Dissociative social interaction, associative social interaction includes (1) cooperation in carrying out associative social interactions, (2) accommodation of students' abilities in correcting problems, (3) assimilation in the form of pointing out solutions in problem-solving, while dissociative social interactions include (1) competition showing bad competitive attitudes, prejudice, and unfair competition, (2) controversy which includes critical power, impolite behavior, as well as giving a bad influence (3) opposition, including an attitude of being against and ignoring other people. Factors that greatly influence social interaction are the provision of direct suggestions by parents, teachers, and friends and the efforts taken by the school through extracurricular programs and special assistance.